2017
DOI: 10.1113/jp274083
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of extracellular Ca2+ binding to specific amino acids for heat‐evoked activation of TRPA1

Abstract: Transient receptor potential ankyrin 1 (TRPA1) is a homotetrameric non-selective cation-permeable channel that has six transmembrane domains and cytoplasmic N- and C-termini. The N-terminus is characterized by an unusually large number of ankyrin repeats. Although the 3-dimensional structure of human TRPA1 has been determined, and TRPA1 channels from insects to birds are known to be activated by heat stimulus, the mechanism for temperature-dependent TRPA1 activation is unclear. We previously reported that extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…73 Furthermore, comparative and mutagenesis analyses using TRPA1s from green anoles, rat snakes, and chickens showed that three negatively charged amino acids near the outer pore vestibule are involved in heat-evoked activation of TRPA1. 74 Presumably, calcium ions would neutralize these negatively charged amino acids to allow heat-induced opening of the channel pore. Thus, species diversity of thermoTRP channels provides informative clues for identifying critical amino acids involved in the activation and inhibitory action of these channels.…”
Section: Thermosensitive Transient Receptor Potential Channels As Thementioning
confidence: 99%
“…73 Furthermore, comparative and mutagenesis analyses using TRPA1s from green anoles, rat snakes, and chickens showed that three negatively charged amino acids near the outer pore vestibule are involved in heat-evoked activation of TRPA1. 74 Presumably, calcium ions would neutralize these negatively charged amino acids to allow heat-induced opening of the channel pore. Thus, species diversity of thermoTRP channels provides informative clues for identifying critical amino acids involved in the activation and inhibitory action of these channels.…”
Section: Thermosensitive Transient Receptor Potential Channels As Thementioning
confidence: 99%
“…In contrast, mutagenesis or deletion studies have identified several regions that are important for heat-dependent activation throughout TRPV1 and other heat-activated TRP channels. These regions include the N-terminal ankyrin repeat domains in TRPA1 ( 9 ), a membrane-proximal N-terminal segment for TRPV1, TRPV2, and TRPV3 ( 10 , 11 ), the C terminus of TRPV1 ( 12 15 ), and the pore domain in TRPV1 ( 16 19 ), TRPV3 ( 20 ), and TRPA1 ( 21 , 22 ) channels. Indeed, it has been proposed that residues involved in temperature sensing may be scattered throughout the receptor rather than forming a defined temperature-sensing domain ( 23 ).…”
mentioning
confidence: 99%
“… 15 , 16 ) Number of studies have revealed controversy concerning temperature sensitivity of TRPA1 channels, raising a possibility that TRPA1 is more important in heat sensation than cold sensation. 17 19 ) TRPA1 is also robustly activated by electrophiles following covalent modification of cysteine (Cys) residues within the ankyrin repeat domain (ARD). 20 , 21 )…”
Section: Redox Sensitive Trp Channelsmentioning
confidence: 99%